High Security RF Remote Controller - Thang, Pham Manh; Quyen, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 29 No 1, 2013)
Abstract : Remote control via RF or IR is popular for many applications, including vehicle alarms and automatic garage doors. Conventional remote control systems are based on unidirectional transmission and have limited security. More sophisticated devices based on bi-directional transmission are also available but, because of their high cost and certain practical disadvantages, they are not widely used in commercial remote control devices. The popular unidirectional transmission systems currently have two very important security shortcomings: the codes they transmit are usually ﬁxed and the number of possible code combinations is relatively small.Either of these shortcomings can lead to unauthorizedaccess. These shortcomings provide an opportunity for a sophisticated thief to create a device that ‘grabs’ a transmission and retransmits it later, or a device that quickly ‘scans’ all possible identification codes until the correct one is found. In this paper, an application of code hopping technology will be introduced, in which incorporates high security, a small package outline and low cost, to make this device a perfect solution for unidirectional remote keyless entry systems and access control systems. Keywords : KeeLoq block cipher, cryptanalysis, slide attacks, guess-and-determine attacks